Exploring real-world symptom impact and improvement in well-being domains for tardive dyskinesia in VMAT2 inhibitor-treated patients via clinician survey and chart review - Meyer Jonathan M. MD; Chepke Craig MD; Bera Rimal B. MD; Pérez-Rodríguez M. Mercedes MD, PhD; Lundt Leslie MD; Franey Ericha G. PhD; Dhanda Rahul PhD, MA; Benning Betsy MBA; Bron Morgan PharmD, MS; Yonan Chuck PharmD (American Association of Psychiatric Pharmacists, 2023)
Introduction: Two vesicular monoamine transporter 2 (VMAT2) inhibitors are approved in the United States (US) for the treatment of tardive dyskinesia (TD). There is a paucity of information on the impact of VMAT2 inhibitor treatment on patient social and physical well-being. The study objective was to elucidate clinician-reported improvement in symptoms and any noticeable changes in social or physical well-being in patients receiving VMAT2 inhibitors. Methods: A web-based survey was offered to physicians, nurse practitioners, and physician assistants based in the US who prescribed valbenazine for TD within the past 24 months. Clinicians reported data from the charts of patients who met the inclusion criteria and were allowed to recall missing information. Results: Respondents included 163 clinicians who reviewed charts of 601 VMAT2-treated patients with TD: 47% had TD symptoms in ≥2 body regions, with the most common being in the head or face and upper extremities. Prior to treatment, 93% of patients showed impairment in ≥1 social domain, and 88% were impaired in ≥1 physical domain. Following treatment, among those with improvement in TD symptoms (n = 540), 80% to 95% showed improvement in social domains, 90% to 95% showed improvement in physical domains, and 73% showed improvement in their primary psychiatric condition. Discussion: In VMAT2-treated patients with TD symptom improvement, clinicians reported concomitant improvement in psychiatric disorder symptoms and in social and physical well-being. Regular assessment of TD impact on these types of domains should occur simultaneously with movement disorder ratings when evaluating the value of VMAT2 inhibitor therapy.